Nutrient requirements of dairy cattle (Nutrient requirements of domestic animals., 2001)
Deals with the dairy industry. This book allows users to pinpoint nutrient requirements accurately for individual animals. It provides guidance on how nutrient analysis of feed ingredients, insights into nutrient utilization by the animal, and formulation of diets to reduce environmental impacts can be applied to productive management decisions.